Experimental psychopathology paradigms for alcohol use disorders: Applications for translational research. (November 2016) - Bujarski, Spencer; Ray, Lara A.
Abstract: In spite of high prevalence and disease burden, scientific consensus on the etiology and treatment of Alcohol Use Disorder (AUD) has yet to be reached. The development and utilization of experimental psychopathology paradigms in the human laboratory represents a cornerstone of AUD research. In this review, we describe and critically evaluate the major experimental psychopathology paradigms developed for AUD, with an emphasis on their implications, strengths, weaknesses, and methodological considerations. Specifically we review alcohol administration, self-administration, cue-reactivity, and stress-reactivity paradigms. We also provide an introduction to the application of experimental psychopathology methods to translational research including genetics, neuroimaging, pharmacological and behavioral treatment development, and translational science. Through refining and manipulating key phenotypes of interest, these experimental paradigms have the potential to elucidate AUD etiological factors, improve the efficiency of treatment developments, and refine treatment targets thus advancing precision medicine. Highlights: Experimental psychopathology methods represent a cornerstone of alcoholism research. We review major paradigms emphasizing implications, pros/cons and challenges. We review the application of experimental psychopathology to translational research.